2019
DOI: 10.1590/s1984-29612019084
|View full text |Cite
|
Sign up to set email alerts
|

Losses caused by gastrointestinal nematode infections in Dorper lambs under two nutritional status

Abstract: The aim of this study was to evaluate the effect of two nutritional statuses on the productive performance of Dorper lambs naturally infected with gastrointestinal nematodes. Thirty-two lambs, grazing together on the same pasture, were allocated into four experimental groups: (G1) infected-supplemented diet, (G2) control-supplemented diet, (G3) infected-basal diet, and (G4) control-basal diet. Control animals received suppressive treatment with monepantel every two weeks, while precautionary anthelmintic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…These results are in agreement with reports from studies carried out on lambs experimentally infected with H. contortus, in which increased resilience was seen among the supplemented animals (Wallace et al, 1995;Bricarello et al, 2005;Carvalho et al, 2015). In field studies conducted in Brazil on young lambs, benefits from supplementation have also been demonstrated: the animals became more resistant/resilient to natural infections with GINs, with increased productive performance (Louvandini et al, 2006;Melo et al, 2017;Starling et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in agreement with reports from studies carried out on lambs experimentally infected with H. contortus, in which increased resilience was seen among the supplemented animals (Wallace et al, 1995;Bricarello et al, 2005;Carvalho et al, 2015). In field studies conducted in Brazil on young lambs, benefits from supplementation have also been demonstrated: the animals became more resistant/resilient to natural infections with GINs, with increased productive performance (Louvandini et al, 2006;Melo et al, 2017;Starling et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…In a study on grazing Dorper lambs that were naturally infected with GINs and subjected to two nutritional statuses, it was demonstrated that supplemented lambs that underwent suppressive treatment with an anthelmintic (control group) showed a daily body weight gain 17.1% higher than that of the infected group counterpart that underwent targeted selective treatment with an anthelmintic. Among the lambs that received the baseline diet, the difference between the infected and control groups was the largest, at 26.7% (Starling et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body weight reduction was more marked in goats and can be related to the reduced appetite, loss of serum protein and digestion problems linked to disturbances in gastric secretion (Fox 1997). Similar reduction in body weights have been documented by previous studies in sheep and/goat (Kelkele et al 2012;Starling et al 2019).…”
Section: Both Sheep and Goats Have Developed Pathological Changes Due...supporting
confidence: 78%
“…Also drew attention the fact that the treatment against oestrosis did not influence the weight gain of the animals, demonstrating the benign character of the disease in lambs. The treatment with anthelminthics, including in those lambs from control group, avoided the interference of helminthiasis in the body weight gain of the lambs, which were around 190 g per day, within the expected for grass fed male lambs supplemented with concentrate ( 30 ). However, more studies are necessary to evaluate the influence of oestrosis on sheep productivity in our environmental conditions, especially in older animals continuously exposed to the parasitism.…”
Section: Discussionmentioning
confidence: 73%